A desigualdade racial da pobreza no Brasil - Rafael Guerreiro Osorio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This paper describes the evolution of poverty among pretos (black), pardos (brown/mixed) and brancos (white) from 2004 to 2014, and investigates whether along with the already known reduction of poverty in the period there was also reduction of the racial inequality of poverty. To do so, it presents the main indicators of the incidence, intensity and inequality of poverty for a broad set of poverty lines, from US PPP 0.10 to 10.00 per day per person. The indicators are decomposed to ascertain the contribution of each group to overall poverty, and the odds of pretos, pardos and brancos being poor are analyzed. The fall in poverty from 2004 to 2014 as a whole, and separately among pretos, pardos and brancos, was characterized for all lines. This decline was greater among pretos and pardos than among brancos, leading to a decrease in the racial inequality of poverty. Although it has declined, the racial inequality of poverty remains very high. In 2014, the level of poverty indicators for pretos and pardos was almost equal to that of brancos in 2004. In 2004, on the average of the poverty lines considered, the odds of pretos being poor were 2.5 times greater than brancos'; and the odds of pardos was 3.2 times higher. In 2014, the odds of pretos being poor was still 2.1 times greater than brancos', while that of pardos remained 2.6 times greater.
Keywords: I32; 330; poverty; racial inequality